Effect of the Amount of lipids on the growth of Oreochromis Niloticus (L) in Kisangani, (Rdcongo) - Serge Munganga Kabate (Budapest International Research and Critics University, 2022)
A study has been undertaken in Kisangani area using experimentally two different types of feed RO and R12 in order to verify the lipids effect on Tilapia niloticus growth rate. It resulted from the study that Tilapia niloticus has doubled weight during all the experience. According to the t test of STUDENT calculated between the gain of body mass of fish fed with the food R0 supplemented with 12% of palm oil and those fed with the R12 non supplemented diet with palm oil showed a non-significant difference (P<0,05). The SGR (Specific Growth Rate ‘‘SGR’’) appeared meaningfully and significantly correlated to the fed. The addition of the palm oils to the food improves the specific growth rate varying between 2, 62 %. day for the food supplemented with 12% of lipids (palm oil)), and 1, 34%. day for the food without lipids. The results of mortality rate during this experience did not seem being correlated to the different diet but rather to the manipulation of fish and other experimental protocols artefacts. The protein content of the carcasses of Tilapia varied between 0,043% for the food R0 and 0,056% for the food R12. The diet R12 appeared performing compared to the diet R0 according to body protein gain by unit of consumed protein and for the weight gain by unit of consumed protein by Tilapia niloticus.